The impacts of Constitutional Amendment No. 95/2016 on Federal Universities: The road to dismantling (Research, Society and Development, 2022)
This article raises the hypothesis that there is a process of dismantling Federal Universities — from the perspective of public budgets — made possible by the fiscal austerity measures instituted by Constitutional Amendment No. 95/2016, which sought to set a maximum limit on Federal Government expenses for twenty years. Therefore, we sought to analyze a trajectory of 14 years of funding, in order to identify the dismantling of Federal Universities. The period of greatest investment of these Higher Education Institutions was compared with the institution of Reuni, until the period obscured by Constitutional Amendment No. 95/2016. The research, exploratory and descriptive, analyzed the federal government budget expenditures, specifically discretionary expenses, considering the following classifications: Other Current Expenses - OCE (payment for water, energy, internet, outsourced and others) and Investments - INV (construction of buildings and acquisition of equipment, etc.), at Federal Universities throughout Brazil, which, for this research, will be analyzed by region, between the years 2007 and 2021. As a result, it was identified that, in all regions of Brazil, from 2007 to 2021, the federal government budget for Higher Education, about ODC and INV, has been declining, occurring specifically at the end of Dilma's government, but it was in Bolsonaro's government, from 2018 to 2021, that it occurs significant reduction in budgets.